Wildfowl research on the White Sea Coast - Karpovitch, V N; Skokova, N N (Wildfowl, 1962)
The main object of conservation and research in the Kandalaksha Reserve has always been the Eider Somateria mollissima. The ecology of the Eider during the nesting period has previously been investigated in detail. Recent attention is concentrated on the ecology and behaviour of Eiders outside the nesting period: their migration routes, moulting and wintering areas.